The ultimate survival guide - Flynn, Mike (Science of--, 2010)
Top tips for surviving the wilderness (or your back garden). Switch off your computer game, step outside and learn how to: plot a map; make a weather-proof shelter; navigate using the stars; leave tracking signals for others to follow; bake high-energy survival biscuits and more. Ages 7-9 years.